PENGARUH ARUS KAS OPERASI, KEBIJAKAN HUTANG, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Aprilia Dina Isnawati, 08.05.52.0180; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2012)
This research is a research that examined the effect and analyze the cash flow operating, debt policy, profitability and size of dividend policy at a manufacturing company that go public in Indonesia.The population in this research are all listed manufacturing companies in Indonesia Stock Exchange (BEI) in 2008 to 2010. Sampling technique using a purposive sampling with the following criteria: (1) Manufacturing companies listed on the Stock Exchange and publish audited financial statements are consistent and complete in 2008-2010. (2) The financial statements using the currency of Indonesia. (3) Manufacturing companies that distribute dividends in a row. (4) The company manufactures a berutrut net profit in a row. (5) all required data for this study are comprehensive. According to established criteria contained 36 samples. Analysis technique used is multiple regression analysis.The results of this study indicate that the operating cash flow positive and marginally significant and positive influenceÂ  ignifikansehingga profitability can be used to predict the dividend policy. Meanwhile, debt policy and the negative effect of firm size is not significant and therefore can not be used to predict the dividend policy.Keywords: Dividends, Cash Flow Operating , Debt Policy, profitability, size